Controle ativo de ruído em dutos: otimização do posicionamento de sensores receptores - Miranda, João Gabriel Oliveira de (2013)
One of the main difficulties of Active Noise Control (ANC) in Ducts is to develop a methodology that can achieve control in a wide frequency range. However, most studies of ANC are designed to tonal signal and discrete frequencies. When studding a wide range of frequencies, some of these specific frequencies are not achieving the desired control satisfactorily. Therefore this dissertation was developed to meet the meaning of why these particular frequencies are not achieving a satisfactory level of control. Through a bench trial ANC system using an acoustic duct and a signal generator, it was possible to obtain the FRF (Frequency Response Function) and from it analyze and compare which frequencies were working in the areas of Anti-resonance (resulting in poor control) and which were acting in resonance regions (resulting in good control). Optimizing the sensors location receivers (microphones) could reach a larger number of discrete frequencies controlled satisfactorily on a single project CAR. Results, discussion and conclusions are described in this dissertation.